The P2X7 Receptor in Microglial Cells Modulates the Endolysosomal Axis, Autophagy, and Phagocytosis - Campagno, Keith E.; Mitchell, Claire H. (Frontiers in Cellular Neuroscience, 2021)
Microglial cells regulate neural homeostasis by coordinating both immune responses and clearance of debris, and the P2X7 receptor for extracellular ATP plays a central role in both functions. The P2X7 receptor is primarily known in microglial cells for its immune signaling and NLRP3 inflammasome activation. However, the receptor also affects clearance of extracellular and intracellular debris through modifications of lysosomal function, phagocytosis and autophagy. In the absence of agonist, the P2X7 receptor acts as a scavenger receptor to phagocytose material. Transient receptor stimulation induces autophagy and increases LC3-II levels, likely through calcium-dependent phosphorylation of AMPK, and activates microglia to an M1 or mixed M1/M2 state. We show an increased expression of Nos2 and Tnfa and a decreased expression of Chil3 (YM1) from primary cultures of brain microglia exposed to high levels of ATP. Sustained stimulation can reduce lysosomal function in microglia by raising lysosomal pH and slowing autophagosome-lysosome fusion. P2X7 receptor stimulation can also cause lysosomal leakage, and the subsequent rise in cytoplasmic cathepsin B activates the NLRP3 inflammasome leading to caspase-1 cleavage and IL-1β maturation and release. Support for P2X7 receptor activation of the inflammasome following lysosomal leakage comes from data on primary microglia showing IL-1β release following receptor stimulation is inhibited by cathepsin B blocker CA-074. This pathway bridges endolysosomal and inflammatory roles, and may provide a key mechanism for the increased inflammation found in age-dependent neurodegenerations characterized by excessive lysosomal accumulations. Regardless of whether the inflammasome is activated via this lysosomal leakage or the better-known K+-efflux pathway, the inflammatory impact of P2X7 receptor stimulation is balanced between the autophagic reduction of inflammasome components and their increase following P2X7-mediated priming. In summary, the P2X7 receptor modulates clearance of extracellular debris by microglial cells, and mediates lysosomal damage that can activate the NLRP3 inflammasome. A better understanding how the P2X7 receptor alters phagocytosis, lysosomal health, inflammation and autophagy can lead to therapies that balance the inflammatory and clearance roles of microglial cells.